Establishment of diagnostic reference level for routine CT scan examination in Sokoto state, Nigeria - Kabeer, S. M.; Aliyu, S. A.; Umar, F. K.; Kamal, I.; Murat, H.; Muhammad, N. A.; Karim, M. K.A. (EDP Sciences, 2024)
Diagnostic Reference Levels (DRLs) are embedded into the optimization procedure to regulate CT dose and diagnostic quality. The purpose of this research was to establish the local DRLs and radiation dose exposure for CT scans at the Sokoto State Advanced Medical Diagnostic Center, Nigeria. 190 patients who had CT head, chest, and abdomen-pelvis scans were collected and evaluated for this study. It was established that the DRLs for CTDIvol for the head, thorax, and abdomen-pelvis were 48.2, 9.44, and 8.02, respectively with DLP DRLs in mGy.cm were 1044, 372, and 646. When comparing head CTs, our CTDIvol DRL is lower than many international standards, yet our DLP DRL is also below those of other nations. The chest CT DRL from Sokoto state is comparable to the DLP standards of some nations, although its CTDIvol is higher. The abdomen-pelvis CTDIvol DRLs are lower than those of the UK and US, thus necessitating the implementation of a controlled and optimized protocol in order to guarantee patient safety while maintaining image quality.